RELAKSASI IMAN MELALUI SEPAKBOLA RELIGIUS - El-Syam, Robingun Suyud; Muntaqo, Lutfan (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2022)
The article aims to reveal the relaxation of faith through religious football, emphasizing reflective thinking and relaxation. Through a theoretical approach, the research concluded: that religious football is an interpretation of the 5 pillars of Islam and 6 pillars of faith so that the total is 11 so it is the same as a football team. Relaxation of faith through religious football contemplation is carried out by reducing each pillar as part of the dimension of faith which must be transcendent by exercising feelings in every activity of daily life so that everything has the dimension of worship. With this strategy, faith will increase closer to God until it penetrates into the soul which has an impact on calm in life. The research contributes to ways of increasing faith by emphasizing reflective thinking and relaxation.